Initiation of Germination of Bacterial Spores by Hydrostatic Pressure - Gwyn W. Gould; A. J. H. SALE (1970)
SUMMARY: Hydrostatic pressure initiated germination of bacterial spores in nutrient-free media. Those spores which were most dormant towards chemical germinants at I atmosphere pressure were also the most resistant to germination by pressure treatment. Germination by high pressure treatment was characterized by temperature and pH optima, like germination at atmospheric pressure. Germination initiated by pressure was inhibited by metabolic poisons and was potentiated by low concentrations of various nutrients including some of those which are normally germinative (at higher concentrations) at atmospheric pressure. In particular, L-alanine and closely related α-amino acids, but not their breakdown products, potentiated germination initiated by pressure. Study of potentiation by D-alanine (which strongly inhibits germination initiated by L-alanine at I atmosphere pressure) revealed that high pressures caused an increase in the rate of racemization of alanine by spores. Germination by pressure probably resulted from acceleration of some germination reaction which is normally negligibly slow at a pressure of I atmosphere, and also from an increase in permeability of some barrier within the spore to L-alanine and related α-amino acids.